Analysis of Torsion Induced Giant Gyrotropy in Hexagonal CdS and CdSe Crystals - Dimov, Todor; Iliev, Ilia; Hristova, Antonina; Lange, Horst (Advanced Aspects of Engineering Research Vol. 16, 2021)
The symmetry C6v of hexagonal CdS and CdSe crystals exhibits "weak" gyrotropy. In crystals of CdS and CdSe deformed by a torsional moment guided along the optical axis, a significant gyrotropic effect is observed. The Polarizer-Crystal-Analyzer (P-C-A) device is used. Light does not pass through the device (P–C–A) with crossed P and A and an undeformed CdS or CdSe crystal. The crystal's symmetry is reduced to C6, and it gains gyrotropic properties as a result of the torsion. With a deformed CdS or CdSe crystal, the device (P-C-A) starts to miss light. The intensity of the light that passed through the structure (P–C-A) with deformed CdS or CdSe crystal is 85-90% of the incident light intensity for broad values of the torsional moments, according to our research.